2020
DOI: 10.1021/acs.jmedchem.9b02163
|View full text |Cite
|
Sign up to set email alerts
|

TREK Channel Family Activator with a Well-Defined Structure–Activation Relationship for Pain and Neurogenic Inflammation

Abstract: TWIK-related K+ (TREK) channels are potential analgesic targets. However, selective activators for TREK with both defined action mechanism and analgesic ability for chronic pain have been lacking. Here, we report (1S,3R)-3-((4-(6-methylbenzo­[d]­thiazol-2-yl)­phenyl)­carbamoyl)­cyclopentane-1-carboxylic acid (C3001a), a selective activator for TREK, against other two-pore domain K+ (K2P) channels. C3001a binds to the cryptic binding site formed by P1 and TM4 in TREK-1, as suggested by computational modeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…This discrepancy may be due to different sensory modalities and species used in each study. In support of our data, C3001a, a specific activator of TREK-1, reduces nociceptive responses in neuropathic mice (Qiu et al, 2020). Thus, our results imply that spinal TREK-1 maintains an inhibitory tone in normal condition and it reduces allodynic responses in neuropathic rodents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This discrepancy may be due to different sensory modalities and species used in each study. In support of our data, C3001a, a specific activator of TREK-1, reduces nociceptive responses in neuropathic mice (Qiu et al, 2020). Thus, our results imply that spinal TREK-1 maintains an inhibitory tone in normal condition and it reduces allodynic responses in neuropathic rodents.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, our data support the idea that phosphorylation state of spinal TREK‐1 modulates excitability of DRG and/or spinal cord neurons to reduce neuropathic pain. In support of this, the activation of TREK‐1 in reduces excitability in isolated DRG neurons (Qiu et al., 2020).…”
Section: Discussionmentioning
confidence: 90%
“…A recent paper by Qiu et al (2020) , identified Y270 on TREK-1 (Y285 in their human TREK-1 construct, NM_001017425.3), as an important amino acid regulating the effectiveness of the anti-nociceptive activator, C3001a. In our hands, TREK-1 channels with the mutated amino acid Y270A carried negligible current, 3.3 pA pF −1 (95% CI: 2.1 to 4.5, n = 6) in the absence of any activator ( Supplementary Figure S1 ), so it was not possible to determine the effect of this mutation on inhibition by treprostinil.…”
Section: Resultsmentioning
confidence: 99%
“…A tyrosine in the TM4 region (Y270 in the TREK-1 isoform used here) was recently shown to be important in regulating the effectiveness of an anti-nociceptor activator, C3001a ( Qiu et al, 2020 ). We found, however, that this mutation carried negligible current at −40 mV in the absence of a high concentration of a TREK-1 channel activator and thus were unable to test whether it interfered with treprostinil inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation